Sirtuin 1 Regulates Hepatitis B Virus Transcription and Replication by Targeting Transcription Factor AP-1 - Ren, Ji-Hua; Tao, Ying; Zhang, Zhen-Zhen; Chen, Wei-Xian; Cai, Xue-Fei; Chen, Ke; Ko, Ben C. B.; Song, Chun-Li; Ran, Long-Kuan; Li, Wan-Yu; Huang, Ai-Long; Chen, Juan (Journal of Virology, 2014)
Classifications Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI